Consumer knowledge effect on intention to purchase life insurance - Nelson Lajuni; Franklin Hazley Lai; Stephen Sondoh Jr; Rosle Mohidin (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2020)
Package as a financial product, life insurance is created to provide protection to the insured individual from the risk of unfavourable events such as sudden death and total disability of the policyholder that may affect the family that depends on the breadwinner in their lives. Though the market shows improvement in penetration, many still do not own life insurance. Statistically speaking 5 out of 10 Malaysians have yet protected themselves of risk in life. This study applied the modified theory of planned behaviour (TPB) mediation which includes direct and indirect effects of consumer knowledge and consumer attitude towards the intention to purchase life insurance. Non-probability purposive sampling was conducted on civil servants here in Sabah, Malaysia (N = 206) to examine their purchasing intention. The data were analysed by using partial least squares structural equation modelling (PLS-SEM) using SmartPLS 3.0. The results found that consumer knowledge and consumer attitude had significant effects on the purchasing intention of life insurance products. The findings provide a better understanding of the roles of consumer knowledge and consumer attitude on civil servants purchasing intention on life insurance products. Future study should examine how technology such as fintech and Artificial Intelligence will shape the insurance industry, particularly in Malaysia as the world are currently moving towards 4.0 industrial revolution.